Graph Neural Networks for Geometry Design in Plastic Regime - Iparraguirre, Mikel M.; González, David; Alfaro, Iciar; Cueto, Elias (Jornada de Jóvenes Investigadores del I3A, 2024)
In this work, we extend MeshGraphNets to simulate collisions involving plastic material, previously limited to hyperelastic, addressing higher non-linearities and energy dissipation. While previous work estimated only the displacement field, our approach also resolves the complete tensor stress field, under different boundary conditions and geometries.